EMOTIONAL INTELLIGENCE AMONG YOUNG RELIGIOUS - Lazar, Frans Laka (Jurnal Pendidikan dan Kebudayaan Missio, 2015)
Abstract: Emotional Intelligence Among Young Religious. The young religious in formation try to form his/herself to be emotionally matur person in order to face the challenges of his/her vocation and to establish meaningful and harmonious relationships with others. To achieve this goal, formation program offers emotional intelligence to young religious. Emotional intelligence is defined as the ability to know, appraise, and manage one’s emotion. At the same time, it is the ability to perceive and recognize emotional in others, and the ability to regulate emotions in ways that promote emotional growth. It also includes the ability to facilitate thougts. The main components of emotional intelligence are knowing one’s emotion, managing emotion, motivating oneself, recognizing emotion in others, and handling relationship. Keywords: emotional intelligence, formation in religious Abstrak: Kecerdasan Emosional Bagi Para Religius Muda. Para formandi yang berada pada jenjang formasi dasar berusaha membentuk dirinya menjadi pribadi yang lebih matang dan dewasa dalam hal emosi agar mereka mampu menghadapi berbagai tantangan dalam panggilannya dan membina hubungan yang bermakna dan harmonis dengan orang lain. Untuk mencapai tujuan ini, maka program-program formasi menawarkan salah satu tema kepada para formadi yaitu membangun kecerdasan emosi. Dan kecerdasan emosi diartikan sebagai kemampuan untuk mengenal, menilai, dan mengelola perasaan pribadi. Pada saat yang sama, kecerdasan emosi juga berarti kemampuan untuk memahami dan mengakui emosi orang lain, dan kemampuan untuk mengatur emosi agar bertumbuh dengan lebih baik. Kecerdasan emosi juga termasuk kemampuan untuk memperlancar cara berpikir yang sehat/rasional. Komponen-komponen utama kecerdasan emosi adalah mengenali emosi diri, mengelola emosi, memotivasi diri sendiri, mengenali emosi orang lain, dan membina hubungan.  Kata kunci: kecerdasan emosi, pembentukan dalam hidup religius